Expressão imuno-histoquímica da e-caderina e da ß-catenina em carcinoma epidermóide oral com e sem metástase nodal - Lopes, Fernanda Ferreira (2007)
The adhesion molecules E-cadherin and β-catenin have been studied as possible markers to distinguish carcinomas with and without metastatic potential. The objective of this research was to study the imunohistochemistry expression of the E-cadherin and β-catenin in oral squamous cell carcinoma (OSCC), aiming to contribute for the better understanding of the biological behavior of this lesion. The sample consisted of 30 cases of OSCC, being 15 of tongue and 15 of lower lip. The profile and intensity of labeling and semi quantitative analysis of the percentage of immunopositive tumoral cells in membrane for E-cadherin and β-catenin had been related with the anatomical localization of the lesion, the presence or not of nodal metastasis and the histological grade of malignancy in the invasive front area of the tumor. It was registered the presence or not of cytoplasmic and nuclear labeling of the β-catenin. The results had been submitted to the statistical analysis, being used the Mann-Whitney Test, the Fisher Test and the Spearman Correlation Coefficient (α=0, 05). The results showed that the expression in membrane for E-cadherin and β-catenin was, predominantly, the heterogeneous profile in the lower lip and tongue carcinomas, as well as in the cases with and without nodal metastasis. It was not observed significant statistical difference between expression profile and amount of immunopositive cells for E-cadherin, β-catenin and the anatomical localization of the lesion and for the presence or not of nodal metastasis. However, there was significant difference of the reduced expression of these proteins with the high score of malignancy. It was verified that the expression of the β-catenin in cytoplasm was present in 22 (73.33%) of the 30 analyzed cases, and 6 cases (20%) showed nuclear expression. The statistical analysis detected significant association between the expression of the β-catenin in the cytoplasm with the histological grade of malignancy, being this molecule more frequently present in the cytoplasm in the cases of high score of malignancy. It was concluded that the reduced immunoexpression of these proteins in membrane can be related with the lowest cellular differentiation, as well as with the pattern of invasion in nests and isolated cells, demonstrated in the cases of OSCC with high histological grade of malignancy